Survey of Cover Crop Use on New York Dairy Farms. Issue 1 (1st December 2013) - Long, Emmaline; Ketterings, Quirine; Czymmek, Karl
Abstract : Cover crops have been promoted as a management approach to provide environmental benefits to annual cropping systems and are gaining popularity in New York. Corn ( Zea mays L.) silage rotations in New York may be a particular area where adoption of cover crops should be further promoted. Greater knowledge about successful management practices, soil health improvements, and N management is needed. In this study, 115 New York dairy farmers were surveyed to gain insight into the issues that serve as barriers to adoption of cover crops. Two surveys were developed and targeted to farmers (i) with experience growing cover crops (73 farmers) and (ii) without cover crop experience (42 farmers). Farmers with cover crop experience were motivated to use cover crops to reduce risk of erosion, improve soil organic matter levels, and capture end‐of‐season N. On average, 19% of the total cropland and 48% of the corn acreage were cover cropped annually. Cereal rye ( Secale cereale L.) was the most common cover crop. Timing and costs were raised as barriers for adoption by farmers without cover crop experience. Most farmers who started using cover crops continued to do so; only 14% had discontinued use, citing lack of time and delay in corn planting as reasons. Results of this survey showed potential for expanding acreage of cover crops in New York.